Pengaruh Keragaman Menu, Harga dan Lokasi Terhadap Keputusan Pembelian Pada Yamyam di Kediri - Aliya Fauziah Firulla Bahril Wahdah; Bambang Suwarsono; Brahma Wahyu Kurniawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Very tight competition in the culinary world makes entrepreneurs have to think about what consumers want, including looking at the variety of menus, prices, and locations. The researcher chose Yamyam Restaurant based on several considerations. The purpose of this research is to explain the effect of menu diversity, price, and location partially and simultaneously on purchasing decisions at Yamyam. The research uses quantitative methods. The population taken was 1,277 consumers using Non Probability techniques. The Slovin formula was used for the sample obtained which was 93 respondents. Data processing was conducted with the SPSS program. The results of this study show that menu diversity, prices, and locations have a significant simultaneous effect on purchasing decisions at Yamyam.